A Comprehensive Review on the Role of Antacids in the Management of Stomach Disorders - Khushboo Yadav (International Journal of Toxins and Toxics, 2026)
Antacids are among the most widely used over-the-counter medications for the symptomatic management of acid-related gastrointestinal disorders, including dyspepsia, gastroesophageal reflux disease (GERD), gastritis, and peptic ulcer disease. These agents provide rapid relief by neutralizing gastric hydrochloric acid, thereby increasing intragastric pH and reducing mucosal irritation. In addition to their therapeutic benefits, the long-term and excessive use of antacids may be associated with adverse effects and toxicological concerns, including electrolyte imbalance, metabolic disturbances, drug interactions, and organ-specific complications. This review summarizes the classification, mechanism of action, therapeutic applications, safety profile, adverse effects, and toxicological aspects of commonly used antacids. Furthermore, the review highlights the clinical significance of rational antacid use and emphasizes the importance of monitoring potential toxicity associated with prolonged administration. Understanding both the beneficial and toxicological effects of antacids is essential for optimizing patient outcomes and ensuring safe pharmacotherapy in the management of stomach disorders.
Keywords: Antacids; Dyspepsia; Gastric Acid Neutralization; Gastrointestinal Disorders; Safety Profile; Stomach Disorders; Toxicology; adverse effects; drug interactions; gastroesophageal reflux disease